Can previewing sport-specific video influence reactive-agility response time? - Holding, R.; Meir, R.; Zhou, S. (International Journal of Sports Physiology and Performance, 2017)
The purpose of this study was to examine whether a video-based warm-up could provide an acute performance benefit to response time for athletes in a sport-specific agility task. In addition, 2 learning strategies, explicit and implicit, were compared for their effectiveness in facilitating an improvement in sport-specific agility. Thirty representative male junior rugby union players (age 14-16 y, mean age 14.6 ± 1.09 y) were placed in 3 experimental groups (explicit, implicit, and control) and completed 2 intervention sessions. Testing sessions included preintervention testing, completion of the video-based warm-up intervention, and postintervention testing. A 3D motion-analysis system was used to assess response time in the testing battery. The athletes` response times on the pre- to postintervention tests were compared to determine the effectiveness of the video-based warm-up. A 2-way general linear model with repeated-measures analysis indicated that both the explicit (P = .030, d = 0.28) and implicit (P = .049, d = 0.33) groups significantly improved their response time by the intervention compared with the control group (P = .367, d = 0.08). The mean postintervention response time for the explicit group improved by 19.1% (from 0.246 s pre to 0.199 s post), and the implicit group improved by 15.7% (from 0.268 s to 0.226 s). Findings suggest that a video-based warm-up may provide an acute benefit to sport-specific agility performance for junior athletes.